KEDUDUKAN HUKUM WAKAF TUNAI DALAM TELAAH FIQH MUAMALAH SERTA IMPLEMENTASINYA DALAM HUKUM POSITIF DI INDONESIA - Hayatun Naimah (Universitas Islam Negeri Antasari Banjarmasin, 2015)
Abstract: The issue of cash waqf is not really a new case in the study of fiqh. Historically, cash waqf basically included in the khilafiyah. The legal disagreement occurs as a result of culture and understanding of the legal community is still struggling in the region of fixed asset waqf. There are several answers as well as a legal opinion to be used as proof to some madzhabscholars, one of which is the opinion of Imam Hanafi that allow cash as waqf endowments on the basis of Istihsan bi al-’Urfi.The basic argument of the Hanafi is the hadeeth narrated by Abdullah bin Mas’ud, may Allah be pleased. While, Imam Malik also allow the base diwakafkan quality goods. Beside those arguments, Imam Shafi’i does not allow cash waqf and argue that the cash waqf does not immortal (can disappear). Theseare the law of several fuqaha answers to this problem. While in Indonesia, legally justify the cash waqf with the issuance of Undang-Undang No. 41 Tahun 2004 about Endowments and Peraturan Pemerintah (Government Regulation)No. 42 Tahun 2006 about The Implementation of Undang-Undang No. 41 Tahun2004 which the Regulation Legislation can provide legal certainty on the application and implementation cash waqf in Indonesia. Abstrak :Isu mengenai wakaf tunai sesungguhnya bukanlah perkara baru dalam kajian fiqh. Dalam sejarahnya, wakaf tunai pada dasarnya masuk dalam wilayah khilafiyah. Terjadi silang pendapat hukum tersebut akibat kultur dan pemahaman hukum masyarakat masih bergelut dalam wilayah wakaf tidak bergerak.Ada beberapa jawaban serta pendapat hukum untuk dijadikan hujjah sebagian ulama madzhab, salah satunya ialah pendapatImamHanafi yang membolehkan wakaf tunai sebagai wakaf atas dasar Istihsan bi al-‘Urfi. Dasar argumentasi mazhab Hanafi adalah hadits yang diriwayatkan oleh Abdullah bin Mas’ud, r.a.Sedangkan Imam Malik juga membolehkan dengan dasar kualitas barang yang diwakafkan. Sementara Imam Syafi’i tidak membolehkan wakaf tunai, dengan alasan bahwa wakaf tunai tidak abadi (bisa lenyap).Inilah yang menjadi jawaban hukum dari Fuqahaterhadap permasalahan ini. Sementara di Indonesia, secara yuridis membenarkan adanya wakaf tunai dengan terbitnya Undang-Undang No. 41 tahun 2004 Tentang Wakaf dan Peraturan Pemerintah Nomor 42 Tahun 2006 Tentang Pelaksanaan Undang-Undang 41 tahun2004 yang mana Peraturan Perundang-Undangan ini dapat memberikan kepastian hukum tentang penerapan dan pelaksanaan wakaf tunai di Indonesia.